Extreme Machines - Stevens, Ian. (New York Bearport Publishing Company, Inc., 2006)
Which is more extreme - a car that can go faster than the speed of sound or a nuclear submarine that can run for more than 15 years without refueling? Both are amazing vehicles. Both cost millions of dollars to develop. One, however, is truly more extreme than the other.
Elementary
Keywords: Machinery